Modified graphite material and preparation method thereof
Through the three-stage heating melt coating method and relatively safe resin coating materials, modified graphite materials with high efficiency and safety characteristics are prepared, which solves the safety problems caused by the use of toxic resins in the existing technology and achieves the improvement of material properties. Safety of lifting and preparation processes.
Patent Information
- Application Number
- CN202411856240.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The benzoxazine resin used in the preparation method of existing modified graphite materials is toxic and irritating, resulting in unsafe preparation process and health hazards.
A three-stage heating melt coating method is adopted, using graphite material and phenolic resin or other relatively safe resin coating materials, and preparing modified graphite materials through mixing, melt coating and carbonization steps to ensure uniform and safe coating effect.
Efficient preparation of modified graphite materials is achieved, with large tap density, small specific surface area and high first charge and discharge efficiency, while avoiding the risk of using toxic materials and ensuring the safety of the preparation process.
Smart Images

Figure CN119340389A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a modified graphite material and a preparation method thereof. Background Art
[0002] The negative electrode materials of lithium batteries mainly include carbon-based materials, oxide-based materials, phosphorus-based materials, and silicon-based materials. Among them, carbon-based materials are the most common, which can be further divided into hard carbon, soft carbon, hard-soft composite carbon, graphite, and other carbon materials.
[0003] On the other hand, graphite negative electrode materials have outstanding advantages and obvious disadvantages. The former mainly include: high theoretical lithium insertion capacity, low charge and discharge potential, and a good charge and discharge voltage platform. The latter mainly refers to: general compatibility with the electrolyte, easy expansion and peeling, thereby reducing the capacity of the battery and shortening the effective service life of the battery.
[0004] Therefore, the graphite negative electrode material of lithium batteries is generally modified graphite, and one of the common modification methods is coating, that is, the structural composition of the modified graphite can be divided into a core and a coating layer. Correspondingly, compared with the raw graphite, the modified graphite has a smaller specific surface area (SSA), and the coating layer can cover and repair various defects on the surface of the graphite raw material. Therefore, reflected in the battery performance, the lithium battery corresponding to the modified graphite has a higher first charge and discharge efficiency, referred to as the first efficiency, than the lithium battery corresponding to the graphite raw material. Generally, the first efficiency of the latter is about 89%, and the former can increase this value to 92-94%.
[0005] For example, a Chinese invention patent application with application publication number CN118270782A and application publication date 2024.07.02 discloses a modified graphite material and a preparation method thereof. The preparation method comprises the following steps: first, graphite is added to an oxidant solution of a certain concentration, and the solution is filtered and washed after rapid stirring for a period of time. Then, the graphite oxide and benzoxazine monomer are mixed evenly and melt-coated. Finally, the modified graphite material is obtained by heat treatment in an inert gas.
[0006] The modified graphite material in this invention patent application has the following advantages: low shrinkage of benzoxazine resin during curing and high carbon residue rate after pyrolysis, which can effectively reduce surface defects and specific surface area of graphite, increase the structural density of the surface coating layer, and ultimately improve the initial efficiency and cycle performance of the graphite negative electrode material.
[0007] However, in the actual implementation process, the preparation method still has at least the following shortcomings, namely: The benzoxazine resin material itself is highly toxic, has a strong pungent odor and is corrosive, which can cause irritation to the skin, eyes and respiratory tract. Long-term exposure to benzoxazine resin can cause serious health hazards to the human body. Summary of the invention
[0008] The present invention provides a modified graphite material and a method for preparing the material. The technical problem to be solved by the present invention is: how to make the entire preparation method simpler and safer under the premise of ensuring that the performance of the negative electrode material of the lithium battery is at least not significantly reduced.
[0009] The technical solution adopted by the present invention to solve the above problem is: a modified graphite material, the structure of which is composed of a graphite core and a resin coating layer, and the tap density of the modified graphite material is ≥0.9g / cm 3 Specific surface area ≤3m 2 / g.
[0010] A method for preparing a modified graphite material comprises the following steps in sequence: S1. Mixing: adding graphite material and resin coating material into a mixer, stirring and mixing to obtain a mixture; S2, three-stage temperature rise melt coating: first add the mixed material into the melt coating machine, then carry out three-stage temperature rise stirring coating operation of continuous low temperature, continuous medium temperature and continuous high temperature in an inert gas atmosphere, then stand and keep warm in the continuous high temperature stage, and finally stand and cool to obtain a melt coating material; S3, carbonization: adding the molten coating material into a carbonization furnace, and performing a carbonization operation in an inert gas atmosphere, and then cooling to room temperature to obtain the final modified graphite material.
[0011] A further preferred technical solution is that in S1, the graphite material is artificial graphite or natural graphite, and the resin coating material is a composition of a phenolic resin and a dispersant, or a composition of a urea-formaldehyde resin and a dispersant, or a composition of a silicone resin and a dispersant, or ZCM200, ZCM250, ZCM280 resin-based new negative electrode coating materials produced by Zhejiang Capone New Materials Co., Ltd.
[0012] A further preferred technical solution is that in S1, the weight of the resin coating material is 4-8% of the weight of the graphite material.
[0013] A further preferred technical solution is that in S2, the temperature of the continuous low temperature stage is 180-280°C, the temperature of the continuous medium temperature stage is 300-400°C, and the temperature of the continuous high temperature stage is 350-550°C.
[0014] A further preferred technical solution is that in S2, the heating rate from room temperature to the continuous low temperature stage is 3-5°C / min, the continuous insulation time after the temperature is reached is 3-10min, and stirring is continued during the period; the heating rate from the continuous low temperature stage to the continuous medium temperature stage is 2-4°C / min, the continuous insulation time after the temperature is reached is 3-10min, and stirring is continued during the period; the heating rate from the continuous medium temperature stage to the continuous high temperature stage is 2-4°C / min, the continuous insulation time after the temperature is reached is 1-2h, and stirring is continued during the period; the static insulation time in the continuous high temperature stage is ≥2h.
[0015] A further preferred technical solution is that in S2, the cooling rate to room temperature is ≤20°C / min.
[0016] A further preferred technical solution is that in S3, the temperature of the carbonization operation is 1100-1300°C, the heating rate is 2-10°C / min, and the time is 4-6h.
[0017] Compared with the prior art, the present invention has at least the following beneficial effects: First, the modified graphite material has a relatively large tap density and a relatively small specific surface area, and its preparation method does not contain relatively dangerous raw materials and operating steps, so it has the dual advantages of high efficiency and safety; The second and third stage temperature rise melt coating operations can gradually soften the resin coating material to a molten state while fully contacting and mixing with the graphite material to ensure uniform coating effect; Third, the selection range of its graphite material and resin coating material is relatively large, ensuring that the preparation method has greater practicality; Fourth, the temperature required for the carbonization operation is relatively low, significantly lower than the existing common carbonization temperature of 1500-2500°C, which has the advantages of energy saving and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is an electron microscope photograph of the final modified graphite material in Example 1 of the present invention.
[0019] Figure 2 This is an electron microscope photograph of the graphite material in Example 1 of the present invention.
[0020] Figure 3 This is an electron microscope photograph of the final modified graphite material in Example 2 of the present invention.
[0021] Figure 4 This is an electron microscope photograph of the final modified graphite material in Example 3 of the present invention.
[0022] Figure 5 This is an electron microscope photograph of the final modified graphite material in Comparative Example 1 of the present invention.
[0023] Figure 6 This is an electron microscope photograph of the final modified graphite material in Comparative Example 2 of the present invention.
[0024] Figure 7 This is an electron microscope photograph of the final modified graphite material in Comparative Example 3 of the present invention. DETAILED DESCRIPTION
[0025] The following descriptions are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention.
[0026] Example 1 A modified graphite material comprises a graphite core and a resin coating layer.
[0027] The preparation method of the modified graphite material comprises the following steps in sequence.
[0028] S1. Mixing: adding graphite material and resin coating material into a mixer, stirring and mixing to obtain a mixture, wherein the graphite material is artificial graphite, the resin coating material is a composition of phenolic resin and a dispersant, the dispersant is octadecyl dihydroxyethyl betaine, and the weight of the resin coating material is 4% of the weight of the graphite material.
[0029] S2. Three-stage temperature-increasing melt coating: first add the mixture into the melt coating machine, and then in a nitrogen atmosphere, perform three-stage temperature-increasing stirring coating operations of continuous low temperature, continuous medium temperature and continuous high temperature in sequence, then stand and keep warm in the continuous high temperature stage, and finally stand and cool to obtain a molten coating material, wherein the temperature in the continuous low temperature stage is 250°C, the temperature in the continuous medium temperature stage is 400°C, the temperature in the continuous high temperature stage is 500°C, the heating rate from room temperature to the continuous low temperature stage is 5°C / min, the continuous insulation time after the temperature is reached is 5min, stirring is continued during this period, the heating rate from the continuous low temperature stage to the continuous medium temperature stage is 2°C / min, the continuous insulation time after the temperature is reached is 3min, stirring is continued during this period, the heating rate from the continuous medium temperature stage to the continuous high temperature stage is 4°C / min, the continuous insulation time after the temperature is reached is 2.0h, stirring is continued during this period, the standing insulation time in the continuous high temperature stage is 2h, and the cooling rate to room temperature is ≤20°C / min.
[0030] S3, carbonization: adding the molten coating material into a carbonization furnace, and performing a carbonization operation in an inert gas atmosphere, and then cooling to room temperature to obtain the final modified graphite material, wherein the temperature of the carbonization operation is 1100° C., the heating rate is 8° C. / min, and the time is 6 hours.
[0031] Example 2 A modified graphite material comprises a graphite core and a resin coating layer.
[0032] The preparation method of the modified graphite material comprises the following steps in sequence.
[0033] S1. Mixing: adding graphite material and resin coating material into a mixer, stirring and mixing to obtain a mixture, wherein the graphite material is artificial graphite, and the resin coating material is ZCM250 resin-based new negative electrode coating material produced by Zhejiang Capone New Materials Co., Ltd., and the weight of the resin coating material is 6% of the weight of the graphite material.
[0034] S2. Three-stage temperature-increasing melt coating: first add the mixture into the melt coating machine, and then in a nitrogen atmosphere, perform three-stage temperature-increasing stirring coating operations of continuous low temperature, continuous medium temperature and continuous high temperature in sequence, then stand and keep warm in the continuous high temperature stage, and finally stand and cool to obtain a molten coating material, wherein the temperature in the continuous low temperature stage is 200°C, the temperature in the continuous medium temperature stage is 300°C, the temperature in the continuous high temperature stage is 380°C, the heating rate from room temperature to the continuous low temperature stage is 4°C / min, the continuous insulation time after the temperature is reached is 5min, stirring is continued during the period, the heating rate from the continuous low temperature stage to the continuous medium temperature stage is 3°C / min, the continuous insulation time after the temperature is reached is 10min, stirring is continued during the period, the heating rate from the continuous medium temperature stage to the continuous high temperature stage is 2°C / min, the continuous insulation time after the temperature is reached is 1.5h, stirring is continued during the period, the standing insulation time in the continuous high temperature stage is 2h, and the cooling rate to room temperature is ≤20°C / min.
[0035] S3, carbonization: adding the molten coating material into a carbonization furnace, and performing a carbonization operation in an inert gas atmosphere, and then cooling to room temperature to obtain the final modified graphite material, wherein the temperature of the carbonization operation is 1200° C., the heating rate is 2° C. / min, and the time is 5 hours.
[0036] Example 3 A modified graphite material comprises a graphite core and a resin coating layer.
[0037] The preparation method of the modified graphite material comprises the following steps in sequence.
[0038] S1. Mixing: adding graphite material and resin coating material into a mixer, stirring and mixing to obtain a mixture, wherein the graphite material is natural graphite, the resin coating material is a composition of silicone resin and a dispersant, the dispersant is octadecyl dihydroxyethyl betaine, and the weight of the resin coating material is 8% of the weight of the graphite material.
[0039] S2. Three-stage temperature-increasing melt coating: first add the mixture into the melt coating machine, and then in a nitrogen atmosphere, perform three-stage temperature-increasing stirring coating operations of continuous low temperature, continuous medium temperature and continuous high temperature in sequence, then stand and keep warm in the continuous high temperature stage, and finally stand and cool to obtain a molten coating material, wherein the temperature in the continuous low temperature stage is 190°C, the temperature in the continuous medium temperature stage is 360°C, the temperature in the continuous high temperature stage is 510°C, the heating rate from room temperature to the continuous low temperature stage is 4°C / min, the continuous insulation time after the temperature is reached is 4min, stirring is continued during the period, the heating rate from the continuous low temperature stage to the continuous medium temperature stage is 3°C / min, the continuous insulation time after the temperature is reached is 7min, stirring is continued during the period, the heating rate from the continuous medium temperature stage to the continuous high temperature stage is 3°C / min, the continuous insulation time after the temperature is reached is 1.5h, stirring is continued during the period, the standing insulation time in the continuous high temperature stage is 4h, and the cooling rate to room temperature is ≤20°C / min.
[0040] S3, carbonization: adding the molten coating material into a carbonization furnace, and performing a carbonization operation in an inert gas atmosphere, and then cooling to room temperature to obtain the final modified graphite material, wherein the temperature of the carbonization operation is 1300° C., the heating rate is 5° C. / min, and the time is 5 hours.
[0041] Comparative Example 1 The modified graphite material and preparation method thereof in this comparative example are different from those in Example 1 in only one aspect as follows.
[0042] The above three-stage temperature-increasing melt cladding is replaced by a one-step melt cladding. The details are as follows: The mixture is first added to the melt coating machine, and then heated and stirred, and then allowed to stand and keep warm at the end temperature of the heating operation, and finally allowed to stand and cool to obtain a melt coating material, wherein the end temperature is 500°C, the heating rate from room temperature to 500°C is 5°C / min, the insulation time after the temperature is reached is 1.0h, during which stirring is continued, and then allowed to stand and keep warm for 2h, and the cooling rate to room temperature is ≤20°C / min.
[0043] Comparative Example 2 The modified graphite material and preparation method thereof in this comparative example are different from those in comparative example 1 in only one respect: The above-mentioned heating rate of 5°C / min can be reduced to 1°C / min, which greatly prolongs the melt coating time.
[0044] Comparative Example 3 The modified graphite material and preparation method thereof in this comparative example are different from those in Example 1 in only one respect: The temperature of the carbonization operation is increased from 1100°C to 1800°C.
[0045] Performance Testing The graphite material in Example 1, and the modified graphite materials in the three examples and the three comparative examples were subjected to at least 10 parameter measurements and at least 3 first-effect measurements, and the average values were finally taken and recorded in Table 1.
[0046] The Malvern-Mastersizer 3000 laser particle size analyzer was used to measure D10, D50 and D90, the BSD-BET 400 specific surface area analyzer was used to measure SSA, and the button half-cell method was used to measure the first effect. The specific operation of the button half-cell method is as follows: First, the modified graphite material in the embodiment / comparative example, carbon black, styrene-butadiene rubber, and hydroxymethyl cellulose were added in a weight ratio of 95.5 / 1.5 / 1.5 / 1.5, and stirred evenly in water to prepare a negative electrode slurry, and then the slurry was coated on a battery-grade copper foil, and dried in a vacuum oven at 110° C. for 4 hours, and the modified graphite negative electrode sheet was prepared by rolling and cutting; Second, the positive electrode is a metal lithium sheet, the diaphragm is polyethylene, and the electrolyte includes 1 mol / L LiPF 6 and ethylene carbonate solvent to prepare a button half-cell.
[0047] Table 1 D10 (μm) D50 (μm) D90 (μm) <![CDATA[TAP(g / cm 3 )]]> <![CDATA[SSA(m 2 / g)]]> First effect Graphite material in Example 1 4.011 13.269 32.960 0.68 9.531 89.9% Example 1 5.079 15.955 36.163 0.99 2.529 92.7% Example 2 6.448 16.285 34.826 0.95 2.270 93.4% Example 3 5.415 17.276 37.386 0.92 2.145 94.1% Comparative Example 1 5.332 16.020 36.295 0.81 3.551 90.6% Comparative Example 2 6.821 17.009 35.696 0.92 3.019 92.8% Comparative Example 3 5.998 17.653 35.558 0.93 2.505 93.0% Data analysis The modified graphite materials in the first and third embodiments all have larger particle sizes compared to the initial graphite materials, indicating the effectiveness of the melt cladding operation; The modified graphite materials in the second and third embodiments have a larger tap density, a smaller specific surface area, and a larger initial effect than the initial graphite material, and the preparation method does not contain relatively dangerous raw materials and operation steps, which is very efficient and safe; Third, the modified graphite material in Comparative Example 1 replaces the above three-stage temperature-increasing melt coating with a one-step melt coating, which results in a decrease in tap density and an increase in specific surface area, indicating that the melt coating effect is not sufficient and uniform compared with Example 1, and accordingly, it is also verified at a relatively low first effect, which indicates the necessity of the above three-stage temperature-increasing melt coating operation; Fourth, the modified graphite material in Comparative Example 2 reduces the heating rate of the one-step melting method to 1°C / min, and finally basically reaches the performance level of the modified graphite material in the embodiment through a relatively slow and long coating method. This also proves the beneficial effect of the three-stage heating melting coating operation from the opposite side. This method has outstanding high efficiency advantages while ensuring the performance of the modified graphite material. Fifth, the modified graphite material in Comparative Example 3 selects the temperature of the carbonization operation as the commonly used 1800°C, but the performance of the modified graphite material is not significantly improved compared with the embodiment. This also proves from the opposite side that the above-mentioned three-stage temperature-raising melt coating operation does not need to be matched with a higher carbonization operation temperature, even a relatively low 1100-1300°C, can fully demonstrate the performance advantages of the modified graphite material, which is sufficiently energy-saving and efficient.
[0048] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various modifications can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present invention. These are all non-creative modifications and are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A modified graphite material, characterized in that: The structure consists of a graphite core and a resin coating layer, and the tap density of the modified graphite material is ≥0.9g / cm 3 Specific surface area ≤3m 2 / g, The method for preparing the modified graphite material comprises the following steps in sequence: S1. Mixing: adding graphite material and resin coating material into a mixer, stirring and mixing to obtain a mixture; S2, three-stage temperature rise melt coating: first add the mixed material into the melt coating machine, then carry out three-stage temperature rise stirring coating operation of continuous low temperature, continuous medium temperature and continuous high temperature in an inert gas atmosphere, then stand and keep warm in the continuous high temperature stage, and finally stand and cool to obtain a melt coating material; S3, carbonization: adding the molten coating material into a carbonization furnace, and performing a carbonization operation in an inert gas atmosphere, and then cooling to room temperature to obtain the final modified graphite material.
2. A modified graphite material according to claim 1, characterized in that: In S1, the graphite material is artificial graphite or natural graphite, and the resin coating material is a composition of a phenolic resin and a dispersant, or a composition of a urea-formaldehyde resin and a dispersant.
3. A modified graphite material according to claim 1, characterized in that: In S1, the weight of the resin coating material is 4-8% of the weight of the graphite material.
4. A modified graphite material according to claim 1, characterized in that: In S2, the temperature of the continuous low temperature stage is 180-280°C, the temperature of the continuous medium temperature stage is 300-400°C, and the temperature of the continuous high temperature stage is 350-550°C.
5. A modified graphite material according to claim 4, characterized in that: In S2, the heating rate from room temperature to the continuous low temperature stage is 3-5℃ / min, and the continuous insulation time after the temperature is reached is 3-10min, during which stirring is continued. The heating rate from the continuous low temperature stage to the continuous medium temperature stage is 2-4℃ / min, and the continuous insulation time after the temperature is reached is 3-10min, during which stirring is continued. The heating rate from the continuous medium temperature stage to the continuous high temperature stage is 2-4℃ / min, and the continuous insulation time after the temperature is reached is 1-2h, during which stirring is continued. The static insulation time in the continuous high temperature stage is ≥2h.
6. A modified graphite material according to claim 1, characterized in that: In S2, the cooling rate to room temperature is ≤20°C / min.
7. A modified graphite material according to claim 1, characterized in that: In S3, the carbonization operation temperature is 1100-1300°C, the heating rate is 2-10°C / min, and the time is 4-6h.
Citation Information
Patent Citations
Method for preparing modified graphite negative electrode material of lithium ion power battery
CN103035919A
Coating-modified anode material of lithium ion battery
CN103633303A
Multielement coated and modified negative electrode material of lithium ion battery and preparation method for negative electrode material
CN106505184A
Method for modifying high-magnification lithium ion battery cathode materials
CN106744916A
Graphite cathode material coating modification method, graphite cathode material and application
CN107482203A